Impact on breeding birds of a semi-offshore island-based windmill park in Åland, Northern Baltic Sea - Tanskanen, Antti (Ornis Svecica, 2012)
Breeding bird populations were monitored at a windmill park on Båtskär in southern Åland archipelago 2006–2011. The area is in the outer archipelago and consists of four islands holding six windmills. The operation of windmills started during fall 2007. An environmental impact assessment for the area was done in 2002. The area holds 850–1050 pairs of breeding birds annually. Two species had significantly decreasing trends, namely herring gull Larus argentatus (annual decrease 6.9 pairs, p=0.003) and lesser black-backed gull Larus fuscus fuscus (annual decrease 2.8 pairs, p=0.004). The reason for the decline of the herring gull population is unlikely to be related to the windmill park. However, the close proximity of a windmill to the breeding colony of lesser black-backed gull has most likely contributed to their decline. Some species like swallow Hirundo rustica, house martin Delichon urbicum and auks Alcidae have benefitted of the construction of the windmill park and utilize new small environments created by the construction.